Forest cover change and water yield in large forested watersheds: A global synthetic assessment. Issue 4 (6th April 2017) - Li, Qiang; Wei, Xiaohua; Zhang, Mingfang; Liu, Wenfei; Fan, Houbao; Zhou, Guoyi; Giles‐Hansen, Krysta; Liu, Shirong; Wang, Yi
Abstract: The effects of forest cover change on water yield have long been studied across the globe. Several reviews have summarized the impacts of forest change and water yield from the small and paired watershed experiments, but no any synthetic assessment has been conducted on the basis of studies of large watersheds (>1, 000 km 2 ). We conducted a synthetic analysis on the basis of the studies from 162 large studied watersheds across the globe to explore how forest cover change affects annual water yield. Our first‐ever assessment confirms that deforestation increases annual water yield and reforestation decreases it, which is consistent with results from paired watershed experiments. More importantly, we found that forest cover and climate variability play a coequal role in annual water yield variations. The effects of forest cover change and climate variability on annual water yield variations can be additive or offsetting. Thus, their interactions can critically determine the magnitudes and directions of water yield changes. We also found that the hydrological sensitivities to forest cover change in smaller and dryer watersheds are higher than those in larger and wetter ones. The implications of these findings for sustainable water and watershed management are discussed in the context of future land cover and climate changes.